Gemini Surfactant Performance Evaluation as Inhibitive action of PAPM for Treatment of AISI steel Corrosion and Studying Temperatures Influence in Acidic Medium - Jerri Meften , Mushtaq (University of Thi-Qar Journal of Science, 2019)
To inhibit corrosion of the AISI 4130 steel in 1M H2SO4 solution at different temperatures, the gemini surfactant was used, namely N,N'-((1,4-phenylenebis(azanediyl)) bis (2-hydroxy propane-3,1-diyl)) bis (N,N-dimethyldecan-1-aminium) (PAPM). The gemini surfactant by electrochemical impedance spectroscopy technique and weight loss method has been evaluated at different temperatures 30, 40 and 50°C. The gemini surfactant showed a very good performance as a corrosion inhibitor in acidic solution, and inhibition efficiency increases with increase inhibitor concentration but decreased with increasing temperatures. Impedance technique results shown, that studied molecule act as mixed-type inhibitor toward AISI steel, also values of standard free energy of adsorption suggest the physisorption and chemisorption were occurred for inhibitor molecules on AISI surface. In addition, the inhibitor adsorption behavior on the AISI surface was investigated at specified temperatures and it coincide with Langmuir’s adsorption isotherm. Furthermore, time effect on corrosion inhibition efficiency was studied where results shown that influence was slight. From quantum calculations, the inhibitor act as soft molecule were noted, also it was shown that the inhibitor more responding for reacting with the AISI surface and prefer the electrophilic attack because it contains on a nucleophilic centers. Experimental inhibition efficiency obtained from both two methods are on a good agreement to each other where optimum efficiency reached 90.32% for weight loss method and 87.17% for EIS technique. On other hand, theoretical inhibition efficiency and experimental inhibition efficiency were in a good agreement to each other, where as theoretical efficiency reached 92.35%.